Analisis Kepuasan Kerja Pegawai Pada Transformasi Balai Besar Guru Penggerak Provinsi Jawa Barat - Martini, Dede Herika; Triatna, Cepi; Rosalin, Elin (Jurnal Tata Kelola Pendidikan, 2023)
This research is entitled "Analysis of Employee Job Satisfaction at the Transformation of the West Java Provincial Teacher Training Center". This study aims to determine employee job satisfaction at the transformation of the West Java Provincial Teacher Training Center, find out the factors that affect employee job satisfaction at the West Java Provincial Teacher Training Center, and formulate strategies to increase employee job satisfaction at the West Java Provincial Teacher Training Center. The method used is a qualitative method with a case study approach. The determination of respondents using snowball sampling technique. The results of this study indicate that employee job satisfaction is felt from the dimensions of the job itself, salary, supervision, coworkers, and working conditions. When referring to the dimensions put forward by Fred Luthans related to the job itself, employees get job satisfaction, but when referring to the main tasks and functions of each employee's job, employees have not received job satisfaction. In addition, from the promotion dimension, employees also have not received job satisfaction. Employee job satisfaction is influenced by internal and external factors. In order to increase job satisfaction, it is necessary to formulate strategies to increase job satisfaction